1999
DOI: 10.1038/sj.bjc.6690298
|View full text |Cite
|
Sign up to set email alerts
|

p21/WAF1 expression as related to p53, cell proliferation and prognosis in epithelial ovarian cancer

Abstract: SummaryThe role and prognostic value of the tumour suppressor p21/WAF1 expression in epithelial ovarian cancer has not yet been defined. Therefore, the expression of p21/WAF1 was assessed immunohistochemically (IHC) in 316 epithelial ovarian malignancies in relation to p53, cell proliferation and patient survival. p21/WAF1 expression was inversely correlated with p53 and cell proliferation. Low p21/WAF1 expression was significantly associated with high grade of the tumour (P = 0.0005), advanced FIGO stage (P =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
66
3
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 35 publications
(43 reference statements)
16
66
3
1
Order By: Relevance
“…This is consistent with findings from several other studies (Baekelandt et al, 1999a(Baekelandt et al, , 1999bDiebold et al, 1996;Herod et al, 1996;Marone et al, 1998) although an inverse correlation between TP53 and BCL-2 (Henriksen et al, 1995) and between TP53 and p21 (Anttila et al, 1999) has also been reported in ovarian tumour tissues. The lack of a correlation between TP53 and its downstream genes may reflect the fact that expression of these genes is also regulated by TP53-independent pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with findings from several other studies (Baekelandt et al, 1999a(Baekelandt et al, , 1999bDiebold et al, 1996;Herod et al, 1996;Marone et al, 1998) although an inverse correlation between TP53 and BCL-2 (Henriksen et al, 1995) and between TP53 and p21 (Anttila et al, 1999) has also been reported in ovarian tumour tissues. The lack of a correlation between TP53 and its downstream genes may reflect the fact that expression of these genes is also regulated by TP53-independent pathways.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with a recent report that also failed to find an association between p21 expression and prognosis or response to platinum-based chemotherapy in specimens from stage III ovarian cancer patients (Baekelandt et al, 1999a). In contrast to these findings Anttila et al (1999) reported that low p21 expression, using a polyclonal antibody, is a marker of poor overall survival.…”
Section: Discussionmentioning
confidence: 66%
“…Some of the examples in Table 3 illustrate the concordance in microarray analysis with previous published reports based on Northern blot analysis and immunohistochemistry. In particular, both CDKN1A (Anttila et al, 1999) and SPARC (Mok et al, 1996) have been shown to be down-regulated in aggressive ovarian cancer and this mirrors the situation revealed by microarray expression analysis in our model. Once again, for these genes the pattern of expression of NOV-31 and TOV-81D are highly similar, and contrast sharply with the aggressive EOC samples.…”
Section: Discussionsupporting
confidence: 60%
“…It is possible to compare the expression pattern of genes previously described in ovarian cancer (Anttila et al, 1999;Asschert et al, 1997;Barboule et al, 1998;Brown et al, 1999;Chambers et al, 1998;Courjal et al, 1996;Huleihel et al, 1997;Mok et al, 1996;Neyns et al, 1996;Tanner et al, 1998;Wysocki et al, 1990) with the expression values generated by microarray analysis. Some of the examples in Table 3 illustrate the concordance in microarray analysis with previous published reports based on Northern blot analysis and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere p21 induction has been observed to be p53-independent in breast cancer (Rey et al, 1998), ovarian cancer (Elbendary et al, 1996;Anttila et al, 1999) and in human leukaemia . Our results suggested a p53-independent mechanism of p21 activation only in a subgroup of patients (Table 3).…”
Section: Discussionmentioning
confidence: 99%